Analisis Strategi Pengelolaan Sumberdaya Rajungan Secara Berkelanjutan Di Perairan Teluk Kelabat Dalam Kabupaten Bangka - Kamandaka Daka; Eva Utami; Kurniawan Kurniawan (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2020)
ABSTRACT Kelabat Bay is located on Northern Part of Bangka Island, Bangka Belitung. Kelabat Bay can be divided into two parts bounded by Tanjung Ruh, that are Teluk Kelabat Luar and Teluk Kelabat Dalam. The purpose of this research is to analyze the strategy of Rajungan sources on the waters of Teluk Kelabat Dalam using SWOT method. This research was conducted in May, 2018 on the waters of Teluk Kelabat Dalam, West Bangka, Bangka Belitung using purposive sampling technique. The data were collected using questionnaires and interviews. The results of this study show that there are three types of Rajungan, they are Rajungan Biasa (Portunus Pelagicus), Rajungan Karang (Charybdis feriata), Rajungan Angin (Podophthalmus vigil). In addition, the results of SWOT method indicate that there are 14 strategies of Rajungan Sources on the waters of Teluk Kelabat Dalam. It can be concluded that these three crabs have the same strategy.